Disk reflection and energetics from the accreting millisecond pulsar SRGA J144459.2−604207 - Malacaria, Christian; Papitto, Alessandro; Campana, Sergio; Di Marco, Alessandro; Di Salvo, Tiziana; Cristina, Baglio Maria; Illiano, Giulia; La Placa, Riccardo; Miraval, Zanon Arianna; Pilia, Maura; Poutanen, Juri; Salmi, Tuomo; et al. (EDP Sciences, 2025)
Context. Accreting millisecond pulsars (AMSPs) are excellent laboratories to study reflection spectra and their features as emission is reflected off an accretion disk truncated by a rapidly rotating magnetosphere near the neutron star surface. These systems also exhibit thermonuclear (type-I) bursts that can provide insights into accretion physics and fuel composition.
Aims. We explore spectral properties of the AMSP SRGA J144459.2−604207 observed during the outburst that recently led to its discovery in February 2024. We aim to characterize the spectral shape of the persistent emission as well as both its continuum and discrete features, and to analyze type-I burst properties.
Methods. We employed XMM-Newton and NuSTAR overlapping observations taken during the most recent outburst from SRGA J144459.2−604207. We performed spectral analysis of the time-averaged persistent (i.e., non-bursting) emission. For this, we first employed a semi-phenomenological continuum model composed of a dominant thermal Comptonization plus two thermal contributions. A separate fit was also performed employing a physical reflection model. We also performed time-resolved spectral analysis of the type-I bursts employing a blackbody model.
Results. We observe a broadened iron emission line, thus suggesting relativistic effects, supported by the physical model accounting for relativistically blurred reflection. The resulting accretion disk extends down to 6 gravitational radii, it is observed at an inclination of ∼53°, and is only moderately ionized (log ξ ≃ 2.3). We observe an absorption edge at ∼9.7 keV that can be interpreted as an Fe XXVI edge blueshifted by an ultrafast (≃0.04c) outflow. Our observations of type-I bursts also allowed us to characterize the broadband emission evolution during the burst. We do not find evidence of photospheric radius expansion. Regarding the burst recurrence time we observe a dependence on the count rate that has the steepest slope ever observed in these systems. We also observe a discrepancy by a factor ∼3 between the observed burst recurrence time and its theoretical expected value, which we discuss in the framework of fuel composition and high neutron star mass scenarios.